Roger That: English for Civil Aviation Pilots in Iceland - Guðný Ósk Laxdal 1993- (2019)
This study focuses on the use and study of English as part of education of civil aviation pilots. It examines civil aviation pilots’ experience of Aviation English and how pilots’ English skills are evaluated. Civil aviation pilots require high cognitive English skills as they work in an international environment where clear communication is crucial. English proficiency has become a requirement for pilots for the last decade. Recent studies have brought light on how language ability is a huge safety matter in aviation. Yet, this language proficiency is often not thought of as a skill that needs to be particularly trained for pilots or other workers in aviation. This particular subject has never been researched before in Iceland. Recent studies on English in Iceland show that English proficiency is not as high as often presumed, and that many struggle when faced with more complex vocabulary and situations than used in everyday life or with entertainment technology. This study shows similar results, as pilots describe hesitation when first using English in radio communication and lack of confidence when speaking with non-Icelandic crew members for a long period. Aviation English requires proficiency in both standard phraseology used in radiotelephony communication, and general English that is used in an international context with speakers of any proficiency around the world. Icelandic pilots struggle with understanding accents in certain areas of the world and describe lack of standardisation both abroad and here in Iceland when using radiotelephony. Icelandic pilot education does not consider English to be a subject or offer any formal training in English for aviation students.